1975
DOI: 10.1111/j.1432-1033.1975.tb03902.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Relationship in the Urokinase Hydrolysis of α‐N‐Acetyl‐l‐lysine Anilides

Abstract: The absence of both nonproductive binding and substrate activation and also the good solubility of the substrates make the urokinase-catalysed hydrolysis of specific anilides a very suitable reaction for substrate structure -enzyme activity studies.Derivatives of a-N-acetyl-L-lysine anilide with high a--value substituents in the aniline ring were synthesized. Rate constants k,,,, and apparent Michaelis-Menten constants K , (app.) are presented. From the substituent dependence of k,,,, and from the fact that k,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The charge (slope) on the nitrogen atom in the anilines containing electron-withdrawing groups is β lg = Ϫ0.25 (correlation coefficient r = 1.00 for the linear regression) and on the nitrogen atom in the anilines containing electrondonating groups is β lg = 0.43 (correlation coefficient r = 0.98 for the linear regression). These data are similar in magnitude to β lg ≈ 0.8 (calculated) 29 and β lg = 1.27 for electron-donating groups 31 in the reaction of chymotrypsin, and β lg ≈ Ϫ0.3 (calculated) 30 for electron-withdrawing groups in the reaction of urokinase.…”
Section: Reaction Of N 4 -(4ј-substituted Phenyl)-l-asparagines With ...supporting
confidence: 73%
See 1 more Smart Citation
“…The charge (slope) on the nitrogen atom in the anilines containing electron-withdrawing groups is β lg = Ϫ0.25 (correlation coefficient r = 1.00 for the linear regression) and on the nitrogen atom in the anilines containing electrondonating groups is β lg = 0.43 (correlation coefficient r = 0.98 for the linear regression). These data are similar in magnitude to β lg ≈ 0.8 (calculated) 29 and β lg = 1.27 for electron-donating groups 31 in the reaction of chymotrypsin, and β lg ≈ Ϫ0.3 (calculated) 30 for electron-withdrawing groups in the reaction of urokinase.…”
Section: Reaction Of N 4 -(4ј-substituted Phenyl)-l-asparagines With ...supporting
confidence: 73%
“…27 Because the mechanism for GA has been proposed to be analogous to serine proteases, we compared our results with the most applicable results reported for rate-limiting acylation reactions utilizing anilides for chymotrypsin 28,29 and urokinase. 30 A biphasic Hammett plot for log (k cat ) vs. σ as in Fig. 2 was suggested for chymotrypsin by Bundy and Moore.…”
Section: Reaction Of N 4 -(4ј-substituted Phenyl)-l-asparagines With ...mentioning
confidence: 82%
“…Free-energy relationships have also been used to characterize the transition state of the rate-limiting step of enzymatic reactions (), involving studies of substituent effects of parent carboxylic acid derivatives ( , ) or leaving groups ( ). Some studies have used amino acid anilide substrates similar to those used herein to study the acylation reactions of cysteine proteases () and serine proteases ( , ). For example, the rate-limiting acylation of the serine protease chymotrypsin by amino acid anilides has been extensively studied and is of particular relevance to our current work.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the rate-limiting acylation of the serine protease chymotrypsin by amino acid anilides has been extensively studied and is of particular relevance to our current work. Notably, it has been shown that the Hammett plot for this reaction curves upward ( ), from a slope of ∼−2 with electron donating substituents (low σ) ( ) to a slope of ∼0.7 for electron withdrawing substituents (high σ) ( , ). This curvature was explained in terms of the effect of the substituent on the degree of protonation of the aniline leaving group realized at the transition state ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation